Water quality at Cai river mouth and Tac river mouth, Nha Trang bay (2015–2019) - Pham Hong, Ngoc; Le Hung, Phu; Do Anh, Van; Nguyen Hong, Thu; Le Trong, Dung; Dao Viet, Ha (Vietnam Journal of Marine Science and Technology, 2022)
Deltas of large rivers, especially in arid areas, have been used in ancient times for agriculture and are densely populated. In recent decades, many river deltas have been experiencing an increasing anthropogenic impact, contamination of watersheds, and marine pollution caused by the offshore extraction of hydrocarbons. Combining of these factors determines a considerable research interest in river mouth areas. This paper presents the annual monitoring data on the water environment of the two mouths of the Cai river and Tac river, Nha Trang bay, during the period 2015–2019. Statistical data showed an increase in dissolved oxygen demand (DO), biological oxygen demand BOD5, and the concentrations of ammonia, Zn and Cu. Seasonal variation revealed that most of studied parameters’ concentrations, especially nutrients, were higher in the rainy season. In contrast, the values of total suspended solids (TSS) and hydrocarbon (Cai River), and petroleum (Tac river) demonstrated a decrease. Generally, the average value of BOD5, concentrations of Cu and Pb at the Cai river mouth were lower than those at the Tac river mouth, whereas the concentration of Zn was higher. Overall, the water environment of both mouths was qualified for aquaculture and aquatic organism preservation purposes except for the case of coliform.